Implementation of Character Education Policies: Pancasila Student Profile Program in Teaching and Learning English at Junior High School 5 Kopang, Lombok, Indonesia - Tahir, Rifki Syahmi; Soepriyanti, Henny; Nurtaat, Lalu; Waluyo, Untung (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This research concerns how Pancasila Student Profile character education policy is implemented in the practice of teaching English at Junior High School 5 Kopang and how the characteristics/figures of character education are integrated and what problems teachers have been facing. The qualitative descriptive approach for this study was achieved by observation, interviews, and questionnaires with the full implementation picture. Some key findings from the study include the elements of the vital Pancasila student profile fitting the British teacher practice-namely, faith and devotion to God, noble character, cooperation, and independence. Therefore, it will definitely make a contribution to implementing curricular studies that incorporate these values, which in turn make sure of the wholistic development in students in relation to Pancasila principles. On the other hand, major challenges singled out to the effective implementation of those attributes for character education include newness of curricula, lack of enough training, and diversity among the students. Teachers are still internalizing the content of the curriculum, for example, at the same time, necessary training is still to be delivered. Moreover, the heterogeneous experiences of students and value learned make it more complicated to implement it. This sucks the success and difficulties right from the professors hence giving a reflection on what works and what does not work in explicit strategies. These results contributed to an increase in character education policy and practice in Indonesian schools so that these types of initiatives could be implemented and maintained more effectively. In the final analysis, these researches will help the researchers form a student with integral personalities with the values of Pancasila that can provide benefits for the society.